Analysis of the cultural policy in the cultural center of Spain of the city of Lima, Peru (1996-2018) - García Quispe, Rosario Del Pilar (2019)
The Cultural Center of Spain in Lima is one of the most dynamic and innovative institutions in the city. Since its creation, it has been continuously working to boost the cultural sector, providing not only a varied program, but also offering training programs that reinforce the potential of citizens. It is one of the cultural spaces with the largest influx of public in the capital, this thanks to its free policy and its inclusive programming within its physical space and outside of it, taking in some opportunities the Lima streets for the realization of its international events. Also, its articulated work with other public and private organizations has brought its artistic proposals closer and encouraged cultural consumption at all levels of society.